Arrestee Drug Abuse Monitoring II in the United States, 2011 - Hunt, Dana ([Verlag nicht ermittelbar], 2013)
The Arrestee Drug Abuse Monitoring II, 2011, is a collection of interview and bioassay data on over 5000 arrestees in 10 United States counties within 48 hours of their arrest. The collection took place between April 1 and September 30, 2011 and represents the fifth year of ADAM II data collection under the sponsorship of the Office of National Drug Control Policy. The 10 current ADAM II sites are: Atlanta, GA (Fulton County); Charlotte, NC (Mecklenburg County); Chicago, IL (Cook County); Denver, CO (Denver County); Indianapolis, IN (Marion County); Minneapolis, MN (Hennepin County); New York, NY (Borough of Manhattan); Portland, OR (Multnomah County); Sacramento, CA (Sacramento County); and Washington, DC (District of Columbia). In 2011, 5,051 interviews and 4,412 urine tests were conducted in the 10 ADAM II sites over 14 consecutive days in each of two calendar quarters between April 1 and September 30. The samples across these sites represent 35,459 adult males arrested in the 10 sites during the data collection period. Demographic variables include arrest date and time, gender, date of birth, number and types of offenses, county of arrest, race, education, work status, and language of interview.